British women amateur filmmakers : national memories and global identities - Motrescu-Mayes, Annamaria; Nicholson, Heather Norris, 1957- (Edinburgh scholarship online., 2018)
The study of amateur filmmaking and media history is a rapidly-growing specialist field, and this ground-breaking book is the first to address the subject in the context of British women's amateur practice.